Detection of Cryptosporidium and Giardia in clinical laboratories in Europe—a comparative study. (30th August 2013) - Manser, M.; Granlund, M.; Edwards, H.; Saez, A.; Petersen, E.; Evengard, B.; Chiodini, P.; Bottieau, E.; ,
Abstract To determine the routine diagnostic methods used and compare the performance in detection of oocysts of Cryptosporidium species and cysts of Giardia intestinalis in faecal samples by European specialist parasitology laboratories and European clinical laboratories. Two sets of seven formalin‐preserved faecal samples, one containing cysts of Giardia intestinalis and the other, containing oocysts of Cryptosporidium, were sent to 18 laboratories. Participants were asked to examine the specimens using their routine protocol for detecting these parasites and state the method(s) used. Eighteen laboratories answered the questionnaire. For detection of Giardia, 16 of them used sedimentation/concentration followed by light microscopy. Using this technique the lower limit of detection of Giardia was 17.2 cysts/mL of faeces in the best performing laboratories. Only three of 16 laboratories used fluorescent‐conjugated antibody‐based microscopy. For detection of Cryptosporidium acid‐fast staining was used by 14 of the 17 laboratories that examined the samples. With this technique the lower limit of detection was 976 oocysts/mL of faeces. Fluorescent‐conjugated antibody‐based microscopy was used by only five of the 17 laboratories. There was variation in the lower limit of detection of cysts of Giardia and oocysts of Cryptosporidium between laboratories using the same basic microscopic methods. Fluorescent‐conjugated antibody‐based microscopy was not superior to light microscopy under the conditions of this study. There is a need for a larger‐scale multi‐site comparison of the methods used for the diagnosis of these parasites and the development of a Europe‐wide laboratory protocol based upon its findings.